POLA ASUH PADA ERA MODERN - Ridwan, Yayan (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2026)
This study aims to analyze the concept of parenting patterns from the perspective of Islamic education and their relevance in the modern era characterized by rapid digital technological development. The family is the first and primary educational institution that plays a strategic role in shaping children’s personality, morality, and religious awareness. In the modern context, parenting is not only focused on fostering faith, moral values, and religious practices, but also requires parents’ ability to address digital challenges through open communication approaches, digital parenting, technological literacy, and the strengthening of 21st-century character skills. This research employs a qualitative approach using a library research method, drawing upon literature in Islamic education, educational psychology, and Qur’anic exegesis related to child-rearing. The findings indicate that effective modern parenting adopts an authoritative style that integrates firmness, warmth, role modeling, habituation of religious values, and adaptation to technological developments. A balanced and adaptive parenting approach is proven to be essential in nurturing children who are faithful, morally upright, and capable of facing global challenges wisely.